الصحة النفسية في البيئات المضطربة: استراتيجيات التكيف ودور الدعم المجتمعي في تعزيز الصمود النفسي (Comprehensive Journal of Science, 2025)
This study aimed to explore mental health in disturbed environments: coping strategies and the role of community support in enhancing psychological resilience. It focused on identifying the most common psychological disorders among individuals living in environments experiencing political, social, or economic disturbances, as well as examining the psychological coping mechanisms they rely on and their effectiveness in mitigating negative psychological effects. The study also investigated the contribution of community support—familial, institutional, and societal—in strengthening the psychological resilience of affected individuals. Finally, it addressed the main cultural and institutional obstacles limiting the effectiveness of psychological interventions and community support in promoting mental health in such environments. The descriptive method was adopted for its suitability to the study objectives.The study revealed the following results:-Anxiety disorders, depression, and post-traumatic stress disorder are among the most common psychological disorders in environments experiencing political, social, or economic turmoil.-Individuals in disturbed environments rely on mechanisms such as social support, religiosity, and positive thinking, which are relatively effective in reducing negative psychological impacts depending on the severity of stress and the availability of a supportive environment.-Community support at various levels contributes to enhancing psychological resilience by providing safety, belonging, and alleviating feelings of isolation and anxiety among affected individuals.-The most significant cultural and institutional obstacles include social stigma, misconceptions about mental health, weak infrastructure, and a shortage of specialized personnel, which reduce the effectiveness of interventions and community support in disturbed environments. These factors can be accurately described using the descriptive method to systematically clarify their impact.
Keywords: Mental Health – Disturbed Environments – Coping Strategies – Community Support – Psychological Resilience.